SISTEM INFORMASI MONITORING PEMBUATAN SERAGAM PADA YAYASAN AL-FAJAR MATARAM - Rochullah, Aulia; Agitha, Nadiyasari; Ratnasari, Dwi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2025)
The Al-Fajar Mataram Foundation, an integrated Islamic school that has levels from Kindergarten, Elementary, and Middle School, is facing problems in the process of loading student uniform data, which is still done manually. This process often causes delays, uncertainty, errors, and a lack of transparency for schools and parents regarding the status of uniform production. To overcome this, it is proposed to develop a